Long-term safety of methylphenidate in children and adolescents with ADHD: 2-year outcomes of the Attention Deficit Hyperactivity Disorder Drugs Use Chronic Effects (ADDUCE) study. (May 2023) - Man, Kenneth K C; Häge, Alexander; Banaschewski, Tobias; Inglis, Sarah K; Buitelaar, Jan; Carucci, Sara; Danckaerts, Marina; Dittmann, Ralf W; Falissard, Bruno; Garas, Peter; Hollis, Chris; Konrad, Kerstin; et al.
Summary: Background: Methylphenidate is the most frequently prescribed medication for the treatment of ADHD in children and adolescents in many countries. Although many randomised controlled trials support short-term efficacy, tolerability, and safety, data on long-term safety and tolerability are scarce. The aim of this study was to investigate the safety of methylphenidate over a 2-year period in relation to growth and development, psychiatric health, neurological health, and cardiovascular function in children and adolescents. Methods: We conducted a naturalistic, longitudinal, controlled study as part of the ADDUCE research programme in 27 European child and adolescent mental health centres in the UK, Germany, Switzerland, Italy, and Hungary. Participants aged 6–17 years were recruited into three cohorts: medication-naive ADHD patients who intended to start methylphenidate treatment (methylphenidate group), medication-naive ADHD patients who did not intend to start any ADHD medication (no-methylphenidate group), and a control group without ADHD. Children with ADHD diagnosed by a qualified clinician according to the DSM-IV criteria and, in the control group, children who scored less than 1·5 on average on the Swanson, Nolan, and Pelham IV rating scale for ADHD items, and whose hyperactivity score on the parent-rated Strengths and Difficulties Questionnaire was within the normal range (<6) were eligible for inclusion. Participants were excluded if they had previously taken any ADHD medications but remained eligible if they had previously taken or were currently taking other psychotropic drugs. The primary outcome was height velocity (height velocity SD score; estimated from at least two consecutive height measurements, and normalised with reference to the mean and SD of a population of the same age and sex). Findings: Between Feb 01, 2012, and Jan 31, 2016, 1410 participants were enrolled (756 in methylphenidate group, 391 in no-methylphenidate group, and 263 in control group). 1070 (76·3%) participants were male, 332 (23·7%) were female, and for eight gender was unknown. The average age for the cohort was 9·28 years (SD 2·78; IQR 7–11). 1312 (93·0%) of 1410 participants were White. The methylphenidate and no-methylphenidate groups differed in ADHD symptom severity and other characteristics. After controlling for the effects of these variables using propensity scores, there was little evidence of an effect on growth (24 months height velocity SD score difference –0·07 (95% CI –0·18 to 0·04; p=0·20) or increased risk of psychiatric or neurological adverse events in the methylphenidate group compared with the no-methylphenidate group. Pulse rate and systolic and diastolic blood pressure were higher in the methylphenidate group compared with the no-methylphenidate group after 24 months of treatment. No serious adverse events were reported during the study. Interpretation: Our results suggest that long-term treatment with methylphenidate for 2 years is safe. There was no evidence to support the hypothesis that methylphenidate treatment leads to reductions in growth. Methylphenidate-related pulse and blood pressure changes, although relatively small, require regular monitoring. Funding: EU Seventh Framework Programme.